Examining green brand approaches in promoting new electric vehicles - Xiaoqing Li; Brahim Chekima; Ming-Fook Lim; Meizhen Pan; Aizah Nadia Aknie Ramlee (Sustainable Futures)
The Chinese new energy vehicle (NEV) market has entered a phase of rapid expansion, forming a stable and sizable user base. Maintaining strong brand relationships with existing users has become a necessary strategy for ensuring sustainable business growth. However, existing research has primarily focused on predicting adoption intentions among potential users, while overlooking the brand-related psychological perceptions and behavioral consequences of current NEV owners. To address this gap, this study draws on the Stimulus–Organism–Response (SOR) framework, self-congruity theory, and the concept of authenticity to empirically investigate the roles of green brand authenticity, the congruence between consumer self-concept and brand image, brand attachment in fostering Word-of-Mouth (WOM) and brand forgiveness. Data were collected from 428 NEV owners through Chinese automotive forums and car enthusiast clubs and analyzed using the PLS-SEM method. The findings reveal that higher perceived brand authenticity leads to stronger brand attachment, subsequently enhancing positive WOM and brand forgiveness. Furthermore, brand attachment mediates the positive effects of actual-self and social-self on WOM and forgiveness. NEV companies should move beyond reliance on one-time purchase behaviors and, through brand communication, respond to consumers’ deep-rooted desires for authenticity and self-expression by building emotionally resonant green brand identities. Policymakers should recognize that relying solely on short-term policy incentives is insufficient; authenticity management and green brand incentive mechanisms are equally essential. The study discusses its limitations and directions for future research.